Penggunaan Kapasitor Untuk Perbaikan Unjuk Kerja Motor Induksi Sebagai Generator = The use of Capasitor to Improve an Induction Motor Performance Being used as a Generator - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
An induction motor can be operated as a generator by driving it above its synchronous speed. The advantages of induction motor used as generator in microhydro plants, comparised to synchronous generator is its low capital cost, low maintenance, easily operation, and readily available in the market in many size. The spesification data of induction motor used in this experiment is : 0,25 HP